Upaya Guru PAI Dalam Menerapkan Psikoedukasi Pembelajaran Terhadap Siswa Broken Home Di SMA Ma’arif Sukorejo - Aminatuz Zuhro (AL-Ikhtiar : Jurnal Studi Islam, 2025)
Students from broken homes tend to face complex psychological challenges, such as the loss of an authority figure, emotional conflict, and even an identity crisis. In this context, Islamic Religious Education (PAI) teachers play a strategic role not only as instructors but also as spiritual and emotional companions for students. Psychoeducation is a relevant approach for building psychosocial resilience and religious character in students experiencing family dysfunction. This study focuses on analyzing how Islamic Religious Education (PAI) teachers implement psychoeducation for students from broken homes at Ma'arif Sukorejo High School and identifying supporting and inhibiting factors in this process. The main questions addressed are: how do Islamic Religious Education (PAI) teachers implement psychoeducation, and what factors influence it. This study used a descriptive qualitative approach. Data collection techniques included observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions based on source triangulation. The results indicate that psychoeducation is implemented through routine religious activities, an empathetic approach, and collaboration with guidance and counseling teachers and homeroom teachers. Supporting factors include the support of the principal, synergy between teachers, and family involvement. Meanwhile, inhibiting factors include teachers' limited competence in psychological approaches, students' fluctuating emotional states, a lack of a personal approach to religious education, and minimal family participation. Integrative psychoeducation based on humanistic and spiritual values has proven effective in fostering personal resilience in students from broken homes.                                                                  Abstrak Siswa yang berasal dari keluarga broken home cenderung menghadapi tantangan psikologis yang kompleks, seperti kehilangan figur otoritas, konflik emosional, hingga krisis identitas. Dalam konteks ini, guru Pendidikan Agama Islam (PAI) memegang peran strategis tidak hanya sebagai pengajar, tetapi juga sebagai pendamping spiritual dan emosional siswa. Psikoedukasi menjadi pendekatan yang relevan untuk membangun ketahanan psikososial dan karakter religius siswa yang mengalami disfungsi keluarga. Fokus penelitian ini adalah menganalisis bagaimana guru PAI melaksanakan psikoedukasi terhadap siswa broken home di SMA Ma’arif Sukorejo, serta mengidentifikasi faktor-faktor pendukung dan penghambat dalam proses tersebut. Pertanyaan utama yang dijawab adalah: bagaimana bentuk pelaksanaan psikoedukasi oleh guru PAI, dan apa saja faktor yang memengaruhinya. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Teknik pengumpulan data meliputi observasi, wawancara mendalam, dan dokumentasi. Analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan berdasarkan triangulasi sumber. Hasil penelitian menunjukkan bahwa psikoedukasi dilaksanakan melalui kegiatan keagamaan rutin, pendekatan empatik, serta kolaborasi dengan guru BK dan wali kelas. Faktor pendukung mencakup dukungan kepala sekolah, sinergi antarguru, dan keterlibatan keluarga. Sementara itu, faktor penghambat meliputi keterbatasan kompetensi guru dalam pendekatan psikologis, kondisi emosional siswa yang fluktuatif, kurangnya pendekatan personal dalam pendidikan agama, dan minimnya partisipasi keluarga. Psikoedukasi yang integratif dan berbasis nilai humanistik serta spiritual terbukti efektif dalam membentuk ketahanan pribadi siswa broken home.